PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP IMPOR KEDELAI DI JAWA TENGAH (PERIODE 2001-2013) - Aulia Rachmanti; Riyadi Riyadi; Suharmanto Suharmanto (JOBS (Jurnal Of Business Studies), 2015)
Central Java is the second largest soybean producing provinces after East Java but still have toimport the soybean. The research is intended to analyze (1) the influence of inflation on soybeanimports of Central Java, (2) the influence of rupiah exchange rate on soybean imports of CentralJava, (3) the influence of inflation and rupiah exchange rate on soybean imports of Central Java.This research uses multiple linear analysis, F-test for simultaneous testing and t-test for partialtesting. This research uses secondary data taken from Statistic Bureau of Central Java. Thesimultaneous results by F-test shows that inflation and rupiah exchange rate significantlyinfluenced Central Java Soybean Imports 2001-2013 period. While the result of t-test showed that inflation is significant on Soybean Imports in Central Java 2001-2013 period but rupiah exchange rate did not significantly influence on Soybean Imports in Central Java 2001-2013period. Keywords: Soybean Imports, Inflation, Rupiah Exchange Rate, Policy, and Central Java.